DETERMINAN FAKTOR PERILAKU MEROKOK TERHADAP KEJADIAN ISPA PADA BALITA DI WILAYAH KERJA PUSKESMAS AEK HABIL KOTA SIBOLGA TAHUN 2023 - Novrika Silalahi; Bahtera Bin David Purba; Nurul Hayati; Sulastri Br Ginting; Ana Apriana (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2023)
Acute Respiratory Infection (ARI) is an infection that occurs in the respiratory tract, both upper and lower respiratory tract which is often found in children, especially children under five yearof age. This infection can cause symptoms of cough, runny nose, and fever that last up to 14 days. The purpose of this study was to determine the relationship between smoking behavior and the incidence of Acute Respiratory Infection (ARI) in children under five year in the working area of the Aek Habil Community Health Center, Kota Sibolga. The type of study used quantitative research with a cross sectional approach. The sample collection technique was carried out using simple random sampling method. The number of samples taken was 88 respondents. This study used statistical test with Chi Square.The results of the study:Shown that there is a relationship between knowledge and the incidence of ARI in children under five year in the work area of the Aek Habil Community Health Center (p=0.004), there is an attitude relationship with the incidence of ARI in children under five year in the work area of the Aek Habil Community Health Center (p=0.001), there is a relationship between action and the incidence of ARI in children under five year in the working area of the Aek Habil Community Health Center (p=0.002). It is hoped that the Community Health Center can provide information to the public, especially parents in order to reduce the incidence of ARI in children under five year and provide counseling about the dangers of smoking which can cause ARI in children under five year by reducing the use of cigarettes around children under five year.